2015
DOI: 10.1097/jto.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

Updated Frequency of EGFR and KRAS Mutations in NonSmall-Cell Lung Cancer in Latin America: The Latin-American Consortium for the Investigation of Lung Cancer (CLICaP)

Abstract: Our findings support the genetic heterogeneity of NSCLC in Latin America, confirming that the frequency of EGFR mutations is intermediate between that observed in the Asian and Caucasian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
127
5
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 27 publications
17
127
5
6
Order By: Relevance
“…KRAS mutations were identified in 20-30% of patients with lung cancer in North American populations (30). The prevalence of KRAS mutations in the present study was less than that observed in the Caucasian group.…”
Section: Discussioncontrasting
confidence: 51%
“…KRAS mutations were identified in 20-30% of patients with lung cancer in North American populations (30). The prevalence of KRAS mutations in the present study was less than that observed in the Caucasian group.…”
Section: Discussioncontrasting
confidence: 51%
“…Interestingly, epidemiological reports have shown a higher EGFR mutation prevalence in our study population (25,26). This can be explained by different exposure factors associated such as wood smoke exposure (27), high prevalence of chronic tuberculosis infection (28) and ethnicity (29).…”
Section: Discussionmentioning
confidence: 79%
“…In lung cancer, previous reports have suggested that the incidence of specific molecular abnormalities may vary between ethnic groups and within the Latin American population [39]. Even though the explanation for this variability is not well understood, it does occur, and therefore we must identify possible factors that may explain the differences in lung cancer, such as differences in environmental hazards exposure, within the same geographic region or even within the same ethnic group [40].…”
Section: Discussionmentioning
confidence: 99%